Irish political parties and policy stances on European integration - BENOIT, Kenneth (Institutional Knowledge at Singapore Management University, 2009)
Support for the political and economic integration of Europe has formed an increasingly important policy issue for Irish political parties as the European Union has grown in importance at both the domestic and European level. This article examines the political positioning of Irish parties on the issue of European integration, comparing these positions across parties and across time. For data, it draws on expert surveys taken at each election since 1992, a time series of coded manifestos as well as a computerized content analysis of the 2007 party manifestos. The article also reports the results of a previously unpublished expert survey of Irish party positions on other political dimensions conducted by the author in 2007.